Gaining Competitive Advantage Through Establishing Offshore Development Centres : A Case Study on Titoonic Asia Sdn. Bhd. - Sheikhalizadeh, Mahdiyeh (2009)
This study analyzes the external and internal environment in which Titoonic Asia is operating. It also proposes some marketimg strategies and recommendations for the management of Titoonic Asia for better selling of their new products and services. Currently, using the usual methods of marketing like advertising are considered costly for the company and part of this study also aims to reduce the costs.